Burkholderia pseudomallei known siderophores and hemin uptake are dispensable for lethal murine melioidosis. - Brian H Kvitko; Andrew Goodyear; Katie L Propst; Steven W Dow; Herbert P Schweizer (Public Library of Science (PLoS), 2012)
Burkholderia pseudomallei is a mostly saprophytic bacterium, but can infect humans where it causes the difficult-to-manage disease melioidosis. Even with proper diagnosis and prompt therapeutic interventions mortality rates still range from >20% in Northern Australia to over 40% in Thailand. Surprisingly little is yet known about how B. pseudomallei infects, invades and survives within its hosts, and virtually nothing is known about the contribution of critical nutrients such as iron to the bacterium's pathogenesis. It was previously assumed that B. pseudomallei used iron-acquisition systems commonly found in other bacteria, for example siderophores. However, our previous discovery of a clinical isolate carrying a large chromosomal deletion missing the entire malleobactin gene cluster encoding the bacterium's major high-affinity siderophore while still being fully virulent in a murine melioidosis model suggested that other iron-acquisition systems might make contributions to virulence. Here, we deleted the major siderophore malleobactin (mba) and pyochelin (pch) gene clusters in strain 1710b and revealed a residual siderophore activity which was unrelated to other known Burkholderia siderophores such as cepabactin and cepaciachelin, and not due to increased secretion of chelators such as citrate. Deletion of the two hemin uptake loci, hmu and hem, showed that Hmu is required for utilization of hemin and hemoglobin and that Hem cannot complement a Hmu deficiency. Prolonged incubation of a hmu hem mutant in hemoglobin-containing minimal medium yielded variants able to utilize hemoglobin and hemin suggesting alternate pathways for utilization of these two host iron sources. Lactoferrin utilization was dependent on malleobactin, but not pyochelin synthesis and/or uptake. A mba pch hmu hem quadruple mutant could use ferritin as an iron source and upon intranasal infection was lethal in an acute murine melioidosis model. These data suggest that B. pseudomallei may employ a novel ferritin-iron acquisition pathway as a means to sustain in vivo growth.